Optimizacija režima odmerjanja vankomicina v Univerzitetnem kliničnem centru Maribor - Cvikl, Maja (Zdravniški vestnik, 2011)
Background: Vancomycin is a glycopeptide antibiotic used in the treatment of severe infections caused by Gram-positive bacteria. To lover the risk of antibiotic resistance, minimize toxic drug effects and to improve clinical effectiveness, it is recommended to monitor trough levels of vancomycin, with the desired range between 10 - 20 mg/l (15 - 20 mg/l for complicated infections). Materials and methods: In the University Medical Center Maribor a new method for monitoring of vancomycin treatment has been accepted. Medical staff can adjust vancomycin dosage regimen using the pharmacokinetic program KINETIDEX. The aim of this study was to evaluate the usability of this program on a population of 28 patients treated with vancomycin in our hospital. After administration of the initial dosage regimen and measuring vancomycin trough level we - when necessary - suggested a new dosage regimen using KINETIDEXr. Results: The most common initial dosage regimen (23 patients out of 28) was 1 g/12 h. 9 patients had an impaired renal function before vancomycin treatment, but only 4 of them received an adjusted initial dosage. In 9 patients a serum sample for determining trough concentration was obtained too early, when steady-state conditions had not been reached yet. 20 out of 28 patients required adjustment of the initial vancomycin dosage regimen - 11 of them needed an increased daily dosage and 9 of them a lower daily dosage. In our research 23 patients out of 28 achieved the desired trough concentrations. In 14 out of 15 patients KINETIDEXr was able to predict a dosage regimen that resulted in the desired trough levels. One patient developed acute kidney failure after initiating vancomycin therapy. Conclusions: Initial dosage regimen of vancomycin should be adjusted based on creatinine clearance - in clinical practice this is not always the case. Three-thirds of patients need modification of the initial vancomycin regimen. Clinical pharmacist can adjust dosage by using pharmacokinetic program KINETIDEXr. For effective dose adjustment of vancomycin, a serum sample shouldbe obtained at appropriate time - just before the application of the next dose at steady-state conditions.
Keywords: antibiotic; antibiotiki; bakterijske infekcije; farmakokinetični program; individualno odmerjanje; nefrotoksičnost; therapy; vankomicin; zdravljenje